Hyperstability of Functional Equation Deriving from Quintic Mapping in Banach Space by Fixed Point Method (European Journal of Pure and Applied Mathematics, 2025)
In this work, we examine the hyperstability of the quintic functional equation$φ(u+3v)-5φ(u+2v)-φ(u-2v)+10φ(u+v)+5φ(u-v)-10φ(u)-120φ(v)=0$,in Banach spaces by means of Brzdȩk's fixed point theorem.
Keywords: quintic functional equation; hyperstability; fixed point; stability